2015
DOI: 10.1111/joic.12227
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Small Vessel Disease With the Paclitaxel Drug‐Eluting Balloon: 6‐Month Angiographic and 1‐Year Clinical Outcomes of the Spanish Multicenter Registry

Abstract: The use of this PEB for the treatment of SMD provides excellent 1-year outcomes with only 4.8% MACE. The need for a bailout BMS was a strong predictor of MACE and TLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 25 publications
4
38
0
Order By: Relevance
“…Only half of the patients underwent angiographic follow-up, revealing an LLL of 0.31 mm. As seen in other studies, bailout BMS implantation predicted both MACE and TLR [47]. …”
Section: Drug-eluting Balloonssupporting
confidence: 81%
See 2 more Smart Citations
“…Only half of the patients underwent angiographic follow-up, revealing an LLL of 0.31 mm. As seen in other studies, bailout BMS implantation predicted both MACE and TLR [47]. …”
Section: Drug-eluting Balloonssupporting
confidence: 81%
“…Several factors might have contributed to these conflicting findings, including differences in bailout rate, predilatation, geographical mismatch, and the type of DEB used. For example, bailout proportion varied between 6% and 36%, and in most cases bailout stenting is associated with a less favorable outcome [37, 46, 47, 49]; however, several prospective registries using SeQuent Please DEB did not find a difference between DEB treatment with or without BMS implantation [35, 39, 41]. Geographical mismatch between the DEB-treated area and BMS implantation seems partly to account for the observed differences, where especially the stent edges are sites of restenosis, and thus geographical mismatch should be avoided, and a BMS only implanted as a part of a bailout strategy [21, 24, 28, 37, 49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2‐year TLF rate in the VSV cohort (6.3%) was slightly higher than that in the SVD cohort, once again underscoring that smaller vessel size may result in worse outcomes. The Spanish Registry published the results of the second‐generation DIOR in 103 patients with disease in vessels with a mean RVD of 1.95 ± 0.32 mm. The rate of MACE at 1 year (4.8%) was similar to that achieved with DCBs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that percutaneous intervention using the paclitaxel‐coated drug eluting balloons (DEB) in selected patients treated for small vessel coronary artery disease leads to excellent immediate results, maintained at 1‐year follow‐up, and we would like to congratulate the authors for their results …”
mentioning
confidence: 99%